GALSR: Geographical Based Adaptive Lifetime Secure Routing Protocol For Wireless Sensor Network (International Journal of Engineering and Computer Science, 2017)
: Wireless sensor networks (WSNs) are potentially increased in research field due to their wide range of application. The topology of advanced WSNs form Multi-Hop WSNs. The Main issues in this topology is location based security and lifetime preserving in energy resources.  In this paper, we projected a Geographical based Adaptive Lifetime Security Routing (GALSR) Protocol and GALSR Algorithm to improve the lifetime and security of WSNs. This algorithm enhanced with Greedy for Shortest path finder and Direct Random Propagation for Random Walking. We then determine that the energy consumption is rigorously disproportional to the uniform energy deployment for the given network topology, which greatly reduces the lifetime of the sensor networks. To resolve this issue, we introduce non-uniform energy deployment to optimize the lifetime and message delivery ratio under same energy resources and security. This energy balancing is set by Energy balance control (EBC)   and security parameter using Metric Energy Balancer (MEB).We validate our finding in both Quantitative and Qualitative measures. Our quantitative measures is shown out of NetSim Simulator similarly our implementation is an best prove for our qualitative measures, Our proposed model shows that we achieved with increased Lifetime, Adaptive Security  and Monetary efficient protocol